If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8c + 5 + -5c + 7 = 36 Reorder the terms: 5 + 7 + 8c + -5c = 36 Combine like terms: 5 + 7 = 12 12 + 8c + -5c = 36 Combine like terms: 8c + -5c = 3c 12 + 3c = 36 Solving 12 + 3c = 36 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3c = 36 + -12 Combine like terms: 12 + -12 = 0 0 + 3c = 36 + -12 3c = 36 + -12 Combine like terms: 36 + -12 = 24 3c = 24 Divide each side by '3'. c = 8 Simplifying c = 8
| 5(2-x)=2(4+3x) | | 12-1x=3x | | 3x+-4+2x=0 | | Ln(x^3)-3=0 | | b/16=5 | | 4(a+12)+5(8)= | | 3/4t-5.8 | | 12x-2=3x+14 | | -2n^2+15n-13=0 | | 154=x^2+15x | | -4y-12x=4 | | 2n^2+15n-13=0 | | 0.4*x=75000 | | a-32=29 | | 3x+14=-82 | | 4x^2-50x+486=0 | | t=16t^2+3136 | | X/2-8=6 | | 7.9+d=12 | | 12x-2=-3x+14 | | 2cos^2x+5cosx+5=0 | | -7-5x=-22 | | 6(1-x)+5=2x+3 | | -x-8+7= | | (x-4)(2x+5)= | | (5+3x)-(10x-15)=-22 | | (5+3x)-(10a-15)=-22 | | 26=g | | 6^9-x=1/36 | | 7-3+5x(6-2)= | | 7x^2-4x-6=0 | | h/-1.05=-o.36 |